Water Vapor in the Asian Summer Monsoon Anticyclone: Comparison of Balloon‐Borne Measurements and ECMWF Data. Issue 13 (11th July 2019) - Brunamonti, S.; Füzér, L.; Jorge, T.; Poltera, Y.; Oelsner, P.; Meier, S.; Dirksen, R.; Naja, M.; Fadnavis, S.; Karmacharya, J.; Wienhold, F. G.; Luo, B. P.; et al.
Abstract: Water vapor (H2 O) is the strongest greenhouse gas in our atmosphere. Hence, accurate measurements and a correct representation in global models of H2 O in the upper troposphere/lower stratosphere (UTLS) are important for understanding and projecting climate. Here we compare balloon‐borne measurements of UTLS H2 O, performed by cryogenic frostpoint hygrometers (CFH) and meteorological radiosondes (Vaisala RS41) during two intensive field campaigns in the Asian summer monsoon anticyclone region, with humidity data from three products of the European Centre for Medium‐range Weather Forecasts (ECMWF): operational analysis and forecast (termed OPERA), ERA‐Interim reanalysis, and the newly released ERA5 reanalysis. Taking CFH as a reference, we show that OPERA and ERA5 provide a more accurate representation of UTLS H2 O than ERA‐Interim. In particular, OPERA and ERA5 similarly overestimate H2 O mixing ratios by on average 0.7–0.8 ppmv (14–15%) and 0.7–0.9 ppmv (15–17%) at pressures 60–100 hPa, respectively, and both provide a good representation of the observed vertical distribution (including fine structures) and natural variability of UTLS H2 O. In contrast, ERA‐Interim underestimates UTLS H2 O by 0.6–1.7 ppmv (14–30%), and it fails to capture relevant features of the vertical distribution of UTLS H2 O. At pressures ( p ) lower than 60 hPa, all three ECMWF products are in good agreement with CFH. Humidity measurements by RS41 show an average dry bias of 0.1–0.5 ppmv (3–9%) compared to CFH for 60–100 hPa, and a moist bias increasing with altitude for p < 60 hPa, exceeding 100% for p < 40 hPa. Key Points: ECMWF operational and ERA5 data show moist bias (14–17%) in UTLS water vapor compared to cryogenic frostpoint hygrometer (CFH) ERA‐Interim data shows dry bias (14–30%) in UTLS water vapor compared to CFH New ERA5 reanalysis provides an improved representation of UTLS water vapor compared to ERA‐Interim reanalysis